Accessibility of Halal certification bodies in Australia: a website content analysis - Shuhaimi, Amarul Arief Mohd; Akanbi, Taiwo O.; Ab Karim, Shahrim; Lee, Eun Kyung; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Arshad, Mohd Mursyid (Taylor and Francis, 2024)
The increasing Muslim population and growing demands for Halal products have necessitated a corresponding growth in Halal certification. While Muslim-majority countries typically practice centralized Halal certification governance, non-Muslim countries, including Australia, have their own unique Halal certification body systems. The Australian Government recognizes 24 Halal certification bodies. Previous studies have primarily focused on the general requirements for certification. In contrast, our study takes a unique and novel approach, attempting to understand each body’s system and accessibility from the point of view of customers and food producers. This novel approach should pique the interest of our audience, as it offers a fresh perspective on a well-studied topic. We implemented website content analyses through website searches and comparative analysis to identify information that can assist Halal product consumers and certification applicants. While most bodies have established guidelines for Halal certification, several areas remain unclear, with no procedures to aid consumers and producers in checking and applying for certifications. Our study identifies these areas for improvement, with the goal of enhancing information accessibility and marketability of these bodies to assist consumers and applicants in obtaining proper guidance on Halal certification. This research is not just theoretical, but it has practical implications that can significantly improve the Halal certification process in Australia, making it more accessible and marketable. This reassurance of practical application should instill confidence in the audience about the relevance and usefulness of the study.